2021
DOI: 10.1007/s00330-021-08240-x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging before breast cancer surgery: results of an observational multicenter international prospective analysis (MIPA)

Abstract: Objectives Preoperative breast magnetic resonance imaging (MRI) can inform surgical planning but might cause overtreatment by increasing the mastectomy rate. The Multicenter International Prospective Analysis (MIPA) study investigated this controversial issue. Methods This observational study enrolled women aged 18–80 years with biopsy-proven breast cancer, who underwent MRI in addition to conventional imaging (mammography and/or breast ultrasonography) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…P2-bMRI may transform breast MRI in a one-stop shop solution providing both diagnostic and predictive/prognostic information. While the indication for preoperative MRI is still the subject of debate, it is already regularly performed in clinical practice [9,10,12]. In these patients, the data required for P2-bMRI are readily available, and costly additional investigations are not required.…”
Section: P2-bmri Investigates the Whole Tumour In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…P2-bMRI may transform breast MRI in a one-stop shop solution providing both diagnostic and predictive/prognostic information. While the indication for preoperative MRI is still the subject of debate, it is already regularly performed in clinical practice [9,10,12]. In these patients, the data required for P2-bMRI are readily available, and costly additional investigations are not required.…”
Section: P2-bmri Investigates the Whole Tumour In Vivomentioning
confidence: 99%
“…The only exception concerns the role of breast MRI in preoperative locoregional staging. The final results of a large multinational investigation (the MIPA study) recently provided important real-world data on this matter [10,12], but this indication remains a matter for debate.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, an observational multicenter international prospective analysis (MIPA) including 5,896 patients from 27 centers found that the MRI group had a higher overall mastectomy rate (36.3% vs. 18.0%, p < 0.001) compared with that of the no-MRI group (mammography with ultrasound) [ 21 ]. They reported that the planned mastectomy rates were 22.4% and 14.4% ( p < 0.001) in the MRI and no-MRI groups, respectively.…”
Section: Effect On Surgical Outcomesmentioning
confidence: 99%
“…Therefore, results of conventional imaging suggested the necessity of mastectomy in 67% of women who finally underwent mastectomy, indicating that MRI was used to confirm a surgeon’s decision to perform mastectomy based on conventional imaging. The additional first-line mastectomy rate after MRI was 11.3%, and the MRI group had a reoperation rate of only 3.2% (8.5% and 11.7%, p < 0.001) [ 21 ]. The results from the MIPA study are in line with those of POMB and IRCIS trials in terms of the reoperation rates, which reduced from 15% to 5% and from 27% to 20%, respectively.…”
Section: Effect On Surgical Outcomesmentioning
confidence: 99%
“…larger and multi-focal tumours, rather than the accuracy of MRI per se. 4 Therefore, careful patient selection for preoperative MRI is key. This is recognised in national guidance, which states that breast MRI is only indicated for loco-regional staging under the following circumstances: 5 1.…”
Section: Introductionmentioning
confidence: 99%